EFFECT OF COMBINED THERAPY USING CHLOROQUINE AND VITAMIN C TO THE PERITONEAL MACROPHAGE FUNCTION IN BALB/C STRAIN MICE INFECTED BY Plasmodium berghei - Fitri, Loeki Enggar; Suhendro, Wongso; Murwani, Sri; Muliartha, I Ketut Gede; Ali, Mulyohadi (Fakultas Kedokteran Universitas Brawijaya, 2003)
In acute infection, malaria will induce cellular immunity by activating T lymphocytes and macrophages cells. This induction indirectly triggers free radicals production in order to eliminate the parasites from red blood cells, however high concentration of thismolecules can cause vital tissue pathological changes on host. In late phase of malarial infection, there are immunosupression on macrophages activity including antigen presenting and secretion of immunoregulated mediator. It has been anticipated, vitamin C as antioxidant would diminish the side effect of thesefree radicals during malarial infection and increase the immunity. To see the effect of combination chloroquin and vitamin C in hastening the recuperative process by decreasing parasitemia and increasing the phagocytosis function of macrofages during Plasmodium berghei infection. This study has been carried out using 3 groups of BALB/c mice, all group were inoculated with 1x107Plasmodium berghei infected red-blood cells. No drug was given on control group (IK). In experimental group we introduced an oral therapy ofchloroquin for 5 days in 1.4 mg/cc dosage and vitamin C for 7 days in 0.2 mg/cc dosages concurrently with a Plasmodium berghei inoculation (IKC). One group was only given chloroquin at the same dosage and no drug was given at the control group (IK).